British Thoracic Society survey of rehabilitation to support recovery of the post-COVID-19 population - John R Hurst; Sally J Singh; Gisli Jenkins; Louise Preston; Charlotte Bolton; Amy C Barradell; Neil J Greening (BMJ Open)
Objective A proportion of those recovering from COVID-19 are likely to have significant and ongoing symptoms, functional impairment and psychological disturbances. There is an immediate need to develop a safe and efficient discharge process and recovery programme. Established rehabilitation programmes are well placed to deliver a programme for this group but will most likely need to be adapted for the post-COVID-19 population. The purpose of this survey was to rapidly identify the components of a post-COVID-19 rehabilitation assessment and elements of a successful rehabilitation programme that would be required to deliver a comprehensive service for those post-COVID-19 to inform service delivery.Design A survey comprising a series of closed questions and a free-text comment box allowing for a qualitative analysis.Setting Online survey.Participants Multiprofessional clinicians across specialties were invited to take part.Results 1031 participants responded from a broad range of specialties. There was overwhelming support for an early posthospital discharge recovery programme to advise patients about the management of fatigue (95% agreed/strongly agreed), breathlessness (94%) and mood disturbances (including symptoms of anxiety and depression, 92%). At the time point of 6–8 weeks, an assessment was considered important, focusing on a broad range of possible symptoms and supporting a return to work. Recommendations for the intervention described a holistic programme focusing on symptom management, return of function and return to employment. The free-text comments added depth to the survey and the need ‘not to reinvent the wheel’ but rather adapt well-established rehabilitation services to individually tailor needs-based care with continued learning for service development.Conclusion The responses indicate a huge interest and the urgent need to establish a programme to support and mitigate the long-term impact of COVID-19 by optimising and individualising existing rehabilitation programmes.